Strategi Pengelolaan Ruang Terbuka Hijau Publik Untuk Mewujudkan Green City (Studi Pada Dinas Cipta Karya Dan Tata Ruang Bidang Pertamanan Dan Pju Kota Batu) - Maulana, Bryan (Jurnal Administrasi Publik, 2015)
Abstract : Strategy of Public Green Space Management to Achieve Green City (Study at  Dinas Cipta Karya dan Tata Ruang bidang Pertamanan and PJU  Batu City). Batu city as a tourism city, developed towards ecotourism urban area. Therefore, structuring and management of its public green urban space is important and it can be a model of proper urban environment structuring and management. The rapid growth of hotel and tourism objects in Batu city makes the city is transforming its green open space into human settlements and buildings. As a result, damage of the city’s ecosystem becomes a main issue in Batu City. The method of this research is qualitative approach. Data are collected from Dinas Cipta Karya and Tata Ruang and BAPPEDA of Batu City. The result of this research is that the government of Batu City has a program called P2HK (Green City Development Program) which conducted by BAPPEDA and actualized by a team consisting of various parties to develop and spread open green space area from 2012 to 2020.The recommendation of this research is the government of Batu City must improve the quality of human resources whether it is the city apparatus or the community in managing open green space and to improve development budget for open green space in order to create more functional green area. Keywords: strategy, public green open spaces, green city Abstrak: Kota Batu sebagai kota wisata, dikembangkan ke arah kawasan kota ekowisata. Oleh karena itu penataan dan pengelolaan ruang terbuka hijau publik di kota Batu adalah hal yang penting dan dapat dijadikan sebagai model penataan dan pengelolaan lingkungan kota. Berkembang pesatnya hotel dan wahana objek wisata buatan membuat kota Batu, merubah lahan-lahan terbuka yang menjadi resapan atau hutan beralih fungsi menjadi pemukiman dan gedung bertingkat.Akibatnya kerusakan ekosistem lingkungan di kota Batu menjadi masalah utama kota Batu. Temuan dari penelitian, pemerintah Kota Batu mempunyai program P2HK (Program Pembangunan Kota Hijau) melalui BAPPEDA dan dikerjakan oleh tim swakelola untuk melakukan rencana kerja pengembangan dan perluasan kawasan ruang terbuka hijau yang harus dikerjakan tahun 2012 sampai 2020. Selanjutnya saran untuk masukan pemerintah Kota Batu dalam pengelolaan ruang terbuka hijau harus meningkatkan kualitas sumber daya manusia dalam pengeloaan ruang terbuka hijau dan meningkatkan anggaran pembangunan ruang terbuka hijau sehingga menambah jumlah keberadaan ruang terbuka hijau sehingga dapat mewujudkan Green City.   Kata Kunci: strategi, ruang terbuka hijau publik, kota hijau